Arahan Mitigasi Bencana Kawasan Rawan Longsor di Kecamatan Tinggimoncong Kabupaten Gowa - Andi Muhammad Iskandar; Syafri Syafri; Muh. Idris Taking (Fakultas Teknik Universitas Bosowa, 2022)
This study aims to determine the level of vulnerability to landslides and to formulate mitigation directions and evacuation routes for landslides. This research is qualitative as a material for consideration as well as reference material in analyzing descriptively. Research variables include determining the level of vulnerability including slope, rainfall, land use, soil type, and geology. Scoring and ovelay (superimpose) analysis methods, in determining the level of vulnerability using the Geographic Information System (ArcGis) application. Based on the results of the overlay (superimpose) and the scoring of each variable resulting in a low level of vulnerability, medium vulnerability, and high vulnerability then disaster mitigation directions are proposed in the form of structural and non-structural mitigation as well as disaster evacuation routes.